2021
DOI: 10.1261/rna.078428.120
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting tRNA chaperones: new players in an ancient game

Abstract: tRNAs undergo an extensive maturation process including posttranscriptional modifications that influence secondary and tertiary interactions. Precursor and mature tRNAs lacking key modifications are often recognized as aberrant and subsequently targeted for decay, illustrating the importance of modifications in promoting structural integrity. tRNAs also rely on tRNA chaperones to promote the folding of misfolded substrates into functional conformations. The best characterized tRNA chaperone is the La protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 141 publications
1
14
0
Order By: Relevance
“…Building on the mechanism of TrmB described here, it will be interesting to analyze in the future whether and how TrmB influences tRNA folding as it likely disrupts critical tertiary interactions in the tRNA elbow region. Thus, TrmB has the potential to also act as a tRNA chaperone as previously reported for E. coli TruB and TrmA ( 32 , 50 , 51 ).…”
Section: Discussionsupporting
confidence: 64%
“…Building on the mechanism of TrmB described here, it will be interesting to analyze in the future whether and how TrmB influences tRNA folding as it likely disrupts critical tertiary interactions in the tRNA elbow region. Thus, TrmB has the potential to also act as a tRNA chaperone as previously reported for E. coli TruB and TrmA ( 32 , 50 , 51 ).…”
Section: Discussionsupporting
confidence: 64%
“…The La protein also has a major non-catalytic role in affecting the pathways of 3' end formation of pre-tRNAs. La protein is an abundant nuclear protein, which binds pre-tRNAs (Rinke and Steitz 1982) at their 3' oligo(U) ends (Stefano 1984;Teplova et al 2006), for review see (Wolin and Cedervall 2002;Maraia and Bayfield 2006;Porat et al 2021). La binding leads to endonucleolytic cleavage of the 3' trailer sequence of the pre-tRNA, and protects the 3' end of the pre-tRNA from exonucleases in S. cerevisiae (Yoo and Wolin 1997).…”
Section: ' Trailer Removal Catalyzed By Different Exonucleases and En...mentioning
confidence: 99%
“…Taken together, this work adds to the growing body of literature on the catalytic-independent functions of RNA modification enzymes (reviewed in (63)). While this raises questions as to the precise function of Bmc1 catalytic activity on the 5’ end of U6, in vitro binding assays showed that catalytic activity of the human MePCE promotes 7SK retention following catalysis (64).…”
Section: Discussionmentioning
confidence: 76%